Analysis of Virtual Learning Environments from a Comprehensive Semiotic Perspective - Gloria María Álvarez Cadavid; Guadalupe Alvarez (Universidad Autónoma de Baja California, 2012)
Although there is a wide variety of perspectives and models for the study of online education, most of these focus on the analysis of the verbal aspects of such learning, while very few consider the relationship between speech and elements of a different nature, such as images and hypermediality. In a previous article we presented a proposal for a comprehensive semiotic analysis of virtual learning environments that more recently has been developed and tested for the study of different online training courses without instructional intervention. In this paper we use this same proposal to analyze online learning environments in the framework of courses with instructional intervention. One of the main observations in relation to this type of analyses is that the organizational aspects of the courses are found to be related to the way in which the input elements for the teaching and learning process are constructed.